Pengendalian Kualitas Produksi Panel Drum Dengan Menggunakan Metode Peta Kontrol Di PT. Atmindo - Yan Hari Tama Nasution; Raspal Singh; Ninny Siregar (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2018)
In course of its production, many factor which can make the downhill quality production, especially in shares produce the component of panel of drum boiler, even part of Quality Control do not want to accept result of the production because assumed by a handicap. Defect type that happened that is porosity, under cut, weld beat And over mop, becoming main problem is defect type of porosity and weld beat of because at most happened knowable after. The control map in the world of Quality Control in company produce that is method solve of problem which is usually used in the field of industrial technique to control the quality of production. So that be story level of mistake or product handicap earn in minimizing till no mistake. In the world of Quality Control production company, this method in the field of the industrial technique in application in its execution and felt by result benefit and to the staff employees also represent an advantage to company minimizing cost of expenditure of purchasing of material and working hours of employees in the event of repetition of component work which is equal to rebought new other material , because effect of the happening of handicap produce.